Traditional Kinulung Craft Weaving of the Dusun Tindal of Kota Belud, Sabah - Salbiah binti Kindoyop; Noria ak Tugang; Humin Jusilin; Junior Kimwah (2018)
Arts and cultural heritage is a potent reflection of the identity of a community. The art of traditional handicraft weaving in any society is dependent on the resources available in his environment and the needs of the particular community. The Dusun Tindal of Kota Belud is rich in weaving craft traditions with kinulung as one of its distinctive products. Kinulung is unique with its own specific purpose and simple design, and has been able to withstand modernisation and change. However, the factors of adaptation, environmental change, and modern technological transformation could pose as threats to the traditional and heritage elements in the production of the kinulung. This study is important as a platform for the promotion of continuity and resilience of the Dusun Tindal heritage. Kinulung documentaton will clarify various aspects of the design and purpose elements of this traditional craft. The study focuses on the design and meaning presented in the kinulung weaving tradition as an object of culture in the community. Material for this study was derived from field work through observations, interviews and notations. The findings of the study indicate that the design and motif of the kinulung reflect the cultural values and local knowledge of the Dusun Tindal.